Recursos didácticos para la asignatura de artes musicales énfasis en instrumentos de viento, y su incidencia en la profesionalización de la carrera de educación básica Universidad Técnica de Cotopaxi extensión La Maná año 2014 - Pilaguano Pilatasig, Wilson Gerardo (2015)
The study is carried out addresses a particularly important issue for Basic Education related to the learning of musical wind instruments, emphasis on the flute; A theoretical study is made it can reveal theoretical foundations serve to support the development of the proposal the educational institution where the research is characterized concrete, empirical instruments to support the need for research and guidance that becomes alternative to the learning of wind instruments and specifically for flute.